Investigating the vibrational dynamics of a 17e(-) metallocarbonyl intermediate using ultrafast two dimensional infrared spectroscopy - Kania, Rafal; Stewart, Andrew I; Clark, Ian P; Greetham, Gregory M; Parker, Anthony W; Towrie, Michael; Hunt, Neil T (Physical chemistry chemical physics : PCCP, 2010)
Ultrafast two dimensional infrared (2D-IR) spectroscopic methods have been used to study the vibrational dynamics of a transient 17e(-) metallocarbonyl species formed following photolysis of the n-propyl-cyclopentadienyl tungsten tricarbonyl dimer [(nPr-Cp)W(CO)(3)](2) in solution. A combination of ground-state 2D-IR and transient 2D-IR techniques has revealed interesting differences in the vibrational relaxation processes of the parent dimer and the monomeric photoproduct that are ascribed to changes in solvent interactions arising from the unsaturated coordination sphere of the intermediate. Additionally, the infrared spectrum of the lesser-populated gauche isomeric form of the dimer in the carbonyl-stretching region has been determined using the presence of off-diagonal peaks in the 2D-IR spectra.